Epidemiological profile of patients hospitalized with Crohn’s disease due to severe acute respiratory infection during the COVID-19 pandemic: a 2-year report from Brazil - Nascimento, Laís Silva; Marson, Fernando Augusto Lima; dos Santos, Raquel de Cássia (Frontiers in Medicine, 2024)
Background and aims The novel coronavirus-induced severe acute respiratory syndrome (COVID-19) led to one of the most significant global pandemics of the 21st century, causing substantial challenges for healthcare systems worldwide, including those in Brazil. This study aimed to investigate the demographic and clinical profiles of hospitalized patients in Brazil who had both COVID-19 and Crohn’s disease (CD) over a 2-year period. Methods An epidemiological analysis was conducted using data from Open-Data-SUS. The study focused on describing the demographic characteristics, clinical manifestations, comorbidities, and hospitalization details of patients afflicted with severe acute respiratory syndrome due to COVID-19 and CD, with the aim of predicting mortality risk. Results The states of São Paulo, Paraná, and Minas Gerais accounted for 50% of the reported COVID-19 cases. The most affected racial group consisted of individuals who self-declared as mixed race. Common comorbidities included heart disease, diabetes mellitus, and obesity. The age group most affected was 25 to 60 years old, particularly among hospitalized patients with both CD and COVID-19 who ultimately succumbed to the illness. A multivariable analysis was conducted to identify the following significant risk factors for death: (a) the presence of neurological disorder (OR = 6.716; 95% CI = 1.954–23.078), (b) the need for intensive care (OR = 3.348; 95% CI = 1.770–6.335), and (c) the need for invasive mechanical ventilation (OR = 59.017; 95% CI = 19.796–175.944). Conclusion There was no discernible gender-based prevalence among hospitalized patients with CD and COVID-19; however, individuals of mixed race were disproportionately affected. The 25 to 60 age group emerged as the most vulnerable demographic group, with high risks of hospitalization and mortality. Moreover, the study highlights the potential for COVID-19 to induce systemic pathologies that may result in long-term degenerative effects and sequelae.